(untitled) - Food and Agriculture Organization of the United Nations (FAO) (Rome, Italy, 2009)
Soaring food prices of 2007-2008 were devastating for the poorest of the poor, we need look no futher than the food riots that upset dozens of countries in that period and the sharp rise in global hunger. All we need to work toward improved response to food security crises
Keywords: Food supply,Cung cấp lương thực; International cooperation,Tổ chức quốc tế